Prefatory Poems and the Openings of Poetry: The Interpoetics of Epistemic Incorporation in the Atlantic World - Hart, Jonathan Locke (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2022)
The French, English, and Spanish wrote poems about the “New World” to represent it as known rather than unknown in the interpoetics of epistemic incorporation—to take the unknown of the Americas between and among these European cultures to make them known in terms of earlier knowledge. This article focuses on prefatory poems (paratext) and the main poem (text), and especially the threshold between these poets, their interpoetics. It also focuses on beginnings as another threshold and moving across and on. To recognize the recognizable, anagnorisis within the known framework—that is what the texts of exploration and encounter, including poetry, tend to do—can involve misrecognition. Examining dedicatory poems, lyric, pageant, and epic, and how the known and the unknown work in the poetics of representation, this article argues that the interpoetics is between poems, between paratext and text, work and world, a mimesis that involves poems begetting other poems and representing reality.